Analisis Pilihan Moda Transportasi Haji Dengan Menggunakan Model Logit Biner - Miro, Fidel; Zulman, Herry (Center for Research and Community Services ITB, 1999)
The Government’s idea to propose Calon Haji (Calhaj) transportation by sea is a good suggestion but needs to be well calculated. Sea transportation has specific and different characteristic than other transportation modes, such as air transportation. At the current economic condition, the availability of sea transportation has become a primary transportation choice, since it is cheaper than air transportation. Using Binary Logit Model Approach, this article discusses the choice of transportation by Calon Haji using Binary Logit Model Approach